The XXL survey: First results and future. Issue 2 (29th March 2017) - Pierre, M.; Adami, C.; Birkinshaw, M.; Chiappetti, L.; Ettori, S.; Evrard, A.; Faccioli, L.; Gastaldello, F.; Giles, P.; Horellou, C.; Iovino, A.; Koulouridis, E.; et al.
Abstract : The XXL survey currently covers two 25 deg 2 patches with XMM observations of ∼10 ks. We summarize the scientific results associated with the first release of the XXL dataset, which occurred in mid‐2016. We review several arguments for increasing the survey depth to 40 ks during the next decade of XMM operations. X‐ray ( z < 2) cluster, ( z < 4) active galactic nuclei (AGN), and cosmic background survey science will then benefit from an extraordinary data reservoir. This, combined with deep multi‐ λ observations, will lead to solid standalone cosmological constraints and provide a wealth of information on the formation and evolution of AGN, clusters, and the X‐ray background. In particular, it will offer a unique opportunity to pinpoint the z > 1 cluster density. It will eventually constitute a reference study and an ideal calibration field for the upcoming eROSITA and Euclid missions.